Leading organization design how to make organization design decisions to drive the results you want - Kesler, Gregory, 1952-; Kates, Amy. (San Francisco : Jossey-Bass, 2011)
"Business leaders recognize the need to continually align their organizations to changes in the marketplace and are seeking guidance from both internal and external practitioners. This book helps consultants, HR and organization development professionals understand the process needed and best practices for implementing, evaluating, and adjusting their organization designs in complex organizations. It offers step-by-step guidance for setting up effective governance and management processes to execute a design, and offers insight into helping leaders gain the skills needed to put the design into action"--
Includes bibliographical references (p. 287-290) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Organizational change; Leadership; Electronic books